Impact of the institutional model on psychiatric patients in Chile from the 19th to 21st centuries: a scoping review - Vivaldi Macho, Ennio; Gomez Barbieri, Gustavo; Lechuga, Hernán; Soto-Suazo, Mauricio (Frontiers in Psychiatry, 2023)
Introduction Various hospital models in mental health have been tested in Chile since its foundation. The institutional model with the Asylum and the Madhouse prevailed during the 19th century and much of the 20th. But deinstitutionalizing all psychiatric patients is the solution? Evidence acquisition: A PubMed, Epistemonikos, Lilacs, and Google scholar Scoping Review was carried out in the last five years, using the PRISMA-P method and the Scoping review search strategy. The MeSH terms ("Psychiatry/history" AND "Chile") OR (" Mental disorders" AND "therapy") search. Finally, papers focused on clinical trial therapy evaluation are excluded and emphasized historical evidence effects. Evidence Synthesis: we identified 35 primary studies, we counted the number of articles included in the review that potentially met our inclusion criteria, and noted how many studies had been missed by our search. We analyzed 10 primary studies and 10 primary historical resources that were included in this study. Conclusion State must become a guarantor and responsible for its psychiatric patients and provide professional and humanitarian support to its patients, be it through community psychiatry, day hospitals, devices such as mental health clinics, and psychiatric institutes dedicated to teaching and research, not leaving patients to the free will of their direct relatives, but rather strengthening the primary care system❖ Historical analysis of the causes, management, and consequences of a mental illness pandemic is crucial.❖The study provides key data on the determinants of health and the organization of variables in the socio-economic system, the organization of health systems, geographical and environmental factors, and genetic factors.❖ Limitations: this scoping review uses both scientific literature sources and gray literature in its preparation, and historical sources derived from universal literature, which adds a subjective component to the appreciation of the authors of their time when describing the epidemiological phenomenon.❖ Final result: we identified 35 primary studies, we counted the number of studies included in the review that potentially met our inclusion criteria, and noted how many studies had been missed by our search. We analyzed 10 secondary studies and 10 primary historical resources, which were included in the scope of this study.